Typology of the urban-rural dynamic for Swiss municipalities - Maria-Pia Gennaio; Boris Gouskov; Ali Ferjani (European Regional Science Association (ERSA), 2010)
One function of the agriculture is to contribute to landscape conservation by maintaining open landscapes and creating landscape diversity. Agricultural policy should sustain this function. In Switzerland, like in other European countries, three main complexity-dimensions hamper policy implementation in this domain: First, the urban land use is spreading out from urban centres and is subtracting precious land for agricultural land use. Because of the pressure of economic development and population growth this process is difficult to steer. Second, this process has a very regional character. Since Swiss agricultural policy is regulated mostly at a national level, regional goals are difficult to achieve. Third, a real coordination between land-use policy and agricultural policy is still missing. Therefore, adequate policy measures for guaranteeing the contribution of agriculture to landscape conservation are needed and innovative approaches and instruments dealing with this complexity are still lacking. Goal of the work is to develop instruments to support policy-makers at national and regional level, to support the integration of the national and regional policy goals and to support the coordination of land-use and agricultural policy. Our methodology is GIS-based and integrates the approach of landscape-functions (De Groot 2006) with a policy-evaluation approach. First, we identify landscape functions related with urban land use (e.g. residential, economical, tourism) and agricultural land use (e.g. food production, leisure, esthetic) at local scale. As a second step we try to evaluate how the land-use development-trend is affecting the landscape qualities formulated in both Swiss Federal Law for Spatial Planning and Swiss Federal Law for Agriculture. This approach permits adding to the policy evaluation precious regional information concerning land-use conflicts and the related landscape functions conflicts. The paper will present preliminary results which will allow the formulation of regional goals for the landscape conservation to be achieved with the implementation of agricultural policy and will facilitate the coordination of land-use planning and agricultural policy. De Groot R., 2006. Function analysis and valutation as a tool to assess land use conflicts in planning for sustainable, multi-functional landscapes. Landscape and Urban Planning (75), 175-186.
Keywords: 330